Successful surgical treatment of massive thrombosis of right parts of the heart in a woman-patient with oncological anamnesis - G. I. Kovtun; M. A. Taranov; L. O. Tkachenko; N. B. Ivaniuk; S. M. Sagura; L. A. Stetsenko (Клінічна хірургія)
Successful surgical treatment of massive thrombosis of right parts of the heart in a woman-patient with oncological anamnesis